Piloting a model-to-data approach to enable predictive analytics in health care through patient mortality prediction. (8th July 2020) - Bergquist, Timothy; Yan, Yao; Schaffter, Thomas; Yu, Thomas; Pejaver, Vikas; Hammarlund, Noah; Prosser, Justin; Guinney, Justin; Mooney, Sean
Abstract: Objective: The development of predictive models for clinical application requires the availability of electronic health record (EHR) data, which is complicated by patient privacy concerns. We showcase the "Model to Data" (MTD) approach as a new mechanism to make private clinical data available for the development of predictive models. Under this framework, we eliminate researchers' direct interaction with patient data by delivering containerized models to the EHR data. Materials and Methods: We operationalize the MTD framework using the Synapse collaboration platform and an on-premises secure computing environment at the University of Washington hosting EHR data. Containerized mortality prediction models developed by a model developer, were delivered to the University of Washington via Synapse, where the models were trained and evaluated. Model performance metrics were returned to the model developer. Results: The model developer was able to develop 3 mortality prediction models under the MTD framework using simple demographic features (area under the receiver-operating characteristic curve [AUROC], 0.693), demographics and 5 common chronic diseases (AUROC, 0.861), and the 1000 most common features from the EHR's condition/procedure/drug domains (AUROC, 0.921). Discussion: We demonstrate the feasibility of the MTD framework to facilitate the development of predictive models on private EHR data, enabled by common data models and containerization software. We identify challenges that both the model developer and the health system information technology group encountered and propose future efforts to improve implementation. Conclusions: The MTD framework lowers the barrier of access to EHR data and can accelerate the development and evaluation of clinical prediction models.